(untitled) (Global Journal of Human-Social Science, 2016)
The objective of this study was to examine land use cover dynamics and its implications in Wallecha Watershed Southern Ethiopia The study referred to have applied perceptions analyses descriptive statistics semi-structured and face to face interviews to identify the causes of the changes The study showed high population pressure which in turn leads to increasing demand for land and trees and change in farming systems poor institutional and socio-economic settings lack of land tenure security and inappropriate land use practices were identified as the reasons for the changes Thus it was understood that LU LC is inevitable that it was occurred at all times in the past are presently ongoing and are likely to continue in the future The changes in LU LC in the study watershed have both positive degrading and negative enhancing impacts on particular environmental and ecological changes of the watershed